WNT signaling in health and disease - Larrain, Juan; Olivares, Gonzalo (Progress in molecular biology and translational science, 2018)
WNT Signaling, Volume 153, the latest release in the Progress in Molecular Biology and Translational Science series, seeks to provide the most topical, informative, and exciting monographs available on a wide variety of research topics related to prions, viruses, bacteria and eukaryotes. The series provides readers with in-depth knowledge of important molecular biological aspects of organismal physiology and function, along with insights into how this knowledge may be applied to understand and ameliorate human disease. Each volume is edited by an internationally recognized expert who selects contributors at the forefront of a field.